Unveiling the unseen: anterior nasal septal schwannoma - Azman, Aeisyah Binti; Gill, Ranveer Singh; Marimuthu, Shashi Gopalan; Kodiappan, Radha; Nair, Sukanya Banerjee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Schwannomas also known as neurilemmomas are slow-growing, encapsulated benign peripheral nerve sheath tumours that arise from Schwann cells. It has no gender or racial predilection and commonly occur between the 3rd to 6th decades. Approximately 45% of schwannomas arise from the head and neck region. Sinonasal and paranasal schwannomas however are relatively rare tumours and not commonly documented, accounting less than 4% of all head and neck schwannomas. Schwannomas arising from the nasal septum are rarely encountered, with only few cases reported. Here we report a case of a 50-year-old lady presented with unilateral nasal congestion and intermittent left sided epistaxis. Physical examination revealed a soft tissue mass occupying the left nasal cavity. A complete tumour excision via endoscopic approach was performed and the histopathologic examination identified the tumour as a schwannoma. A prompt resolution of the symptoms ensued following complete excision of the tumour.